Chronic Lymphocytic Leukemia: Real-World Data From India - Tejaswi, V. (JCO Glob Oncol, 2020)
PURPOSE: Chronic lymphocytic leukemia (CLL) is uncommon in India. There are limited studies on CLL from the Indian subcontinent. METHODS: This was a prospective study (2011-2017) of consecutively diagnosed patients with CLL at a single center. The diagnosis, prognosis, treatment indication, response criteria, and adverse events were recorded as per International Workshop on Chronic Lymphocytic Leukemia guidelines. Biosimilar rituximab dosing (375 mg/m(2)) was fixed for all cycles. Time to next treatment (TTNT) was defined as the time from front-line treatment initiation to next treatment or death from any cause. Overall survival (OS) was defined as the time from treatment initiation until death from any cause. RESULTS: A total of 409 patients with CLL were enrolled over the study period. The median follow-up was 32 months (range, 2-135 months). The median age was 61 years, and 31.8% of patients with CLL were ≤ 55 years of age; 43.3% of patients had a cumulative illness rating scale score ≥ 3. Prognostic fluorescence in situ hybridization data were available in 53.3% of patients. Chlorambucil (94/180; 52.2%) and bendamustine + rituximab (BR; 57/180; 31.6%) were the most common regimens used up front. The overall response rates after front-line therapy were 74.4% and 91.2%, respectively. The TTNT was 33 months and not reached, respectively (P = .001). Grade 3/4 neutropenia and infections were seen in 52.6% and 38.5% of patients receiving BR. The median OS was not reached in both regimens (P = .25). CONCLUSION: Indian patients with CLL are younger in chronological age but have higher morbidity burden. Treatment outcomes with biosimilar fixed-dose BR are comparable to those reported in the literature. Chlorambucil is still a valid option, given the economic burden of the disease and treatment.